Improving employee wellbeing in plantation companies: The role of job crafting capability and work engagement - Darmilisani, Darmilisani; Lumbanraja, Prihatin; Absah, Yeni; Gultom, Parapat (Edelweiss Applied Science and Technology, 2025)
This study seeks to investigate how employees' ability to modify their job roles and their level of work engagement influence their overall well-being. The job crafting framework incorporates the Job Demands-Resources (JD-R) theory, highlighting employees' proactive efforts to enhance their work environment and engagement levels. Additionally, work engagement theory provides insight into the psychological states that foster positive outcomes for employees. Employing a quantitative approach, the study utilizes Structural Equation Modeling (SEM). A sample of 170 staff members from private plantation companies in North Sumatra was selected using proportional random sampling. To obtain empirical data, the researchers employed a structured survey instrument featuring Likert-scale questions designed to measure the primary variables: job crafting competence, work engagement intensity, and aspects of employee well-being. The subsequent analysis involved evaluating both the measurement (outer) model and the structural (inner) model, emphasizing the assessment of construct reliability, validity, and the interrelationships within the structural framework. The results demonstrated that job crafting exerts a statistically significant and favorable influence on employees' well-being. Conversely, while work engagement showed a positive correlation with well-being, this relationship was not statistically significant. These results suggest that employees’ proactive efforts to adapt their jobs—such as increasing resources and introducing challenges aligned with their capabilities—enhance their psychological and social well-being. However, while work engagement, encompassing vigor, dedication, and absorption, contributes to well-being, its impact within the plantation industry context is not statistically significant.